A Isolation of Dental Caries Bacteria from Dental Plaque - Abdulhadi, Ali Mohammed Hussein; Alghanim, Kareem M.; Yassein, Mustafa Mohsen; Khadir, Hommam Mohammed; Abd, Tiba Ahmed; Sahib, Mariam Jassim; Raheem, Zainab Ali (Medical Science Journal for Advance Research, 2025)
Background : Dental caries stands out as a highly prevalent and preventable condition, identified as the leading contributor to oral discomfort and tooth loss. This condition represents a significant public health challenge that obstructs the attainment and preservation of oral health across all age demographics. The WHO has indicated that the global issue of oral disease continues to exist, even with significant advancements in the oral health of populations in various countries. Aim of study : Isolation of Dental Caries Bacteria from Dental Plaque and detection Pattern of resistance to common antibiotics in dental clinics. Methodology : Specimens collection include 75 clinical swabs (45 Male and 25 Female) isolated from dental caries patients who were admitted to Al-Kafeel teaching clinic and outpatient from dentist clinic in AL-Najaf City between November 2022 to January 2023 with age group between 30-70 years. All the specimens were labeled and transported Immediately by sterile transport swabs to the laboratory for Culture and Identification. For each patient, medical records were reviewed, which including name, gender, age, address, hospitalization, and antibiotic receiving. and immediately transport to the old . Results : The study comprised of 75 patients with dental caries , 45 patients were male while 30 patients were female , The swabs taken from dental clinics have been showed that 64 (85.3%) of specimens were gram positive bacteria and only 11 specimens (14.7%) were gram negative bacteria. The result showed that about 64 specimens from totally 75 were gram positive and the most common species were: Streptococcus mutans 20 (26.66%) , Staphylococcus aureus 15 (20%), Lactobacilli 10 (13.33%) , Staphylococcus species 8 (10.66%) , Streptococcus species 5 (6.66%) , Enterococcus faecalis 4(5.33%) , Bacillus species 2 (2.66%) and Micrococcus species 2 (2.66%). Gram negative bacteria that isolated from dental caries were only 11 . The bacterial species were : E. coli 3 (4%), K. pneumonia 2 (2.66%) , P. aeruginosa 2 (2.66%), Moraxella 1 (1.33%) and Acinetobacter baumannii 1 (1.33%). Tow specimens were unknown (2.66%) , Vitek 2 system had no results.